FAKTOR PENYEBAB PERUBAHAN GUNA LAHAN DI JALAN LINGKAR UTARA KOTA PADANG PANJANG - Hamdi Irza; Ibnu Syabri (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2016)
Land is a fixed supply, while demand continues to increase as the dynamics of the urban population. This condition has implications for land-use change toward a more profitable activity economically. It occurs in almost all cities, including the Minangkabau community with communal land system. Globalization and the capitalization of the land led to changes in socio-economic and individualization of land ownership resulting in the erosion of customary rights of the village. It is necessary to find a solution for the utilization of communal land economically viable yet maintain the existing socio-cultural values. One way is to understand the patterns of land use changes that occur along with the factors that play a role in it. Areas susceptible to changes in land use are located at the nodes and links, especially in cities with high economic growth, one of which the city of Padang Panjang are home to study. The analysis showed that the process of individualization of land leads to changes in land use. High economic pressures make customary land is fragmented and changing land use. This process is the result of a decrease in land value due to factors bio-physical and socio-economic fields.